The Correlation of Internship and Career Planning for Student’s in The Department of Beauty and Cosmetology - Merita Yanita; Nizwardi Jalinus; Refdinal Refdinal (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
Internship is one aspect that greatly influences career planning in students. This study aims to determine the correlation between internship and career planning in students of the 2019 class of Cosmetology and Beauty department, Padang State University. This type of research is correlation which has two variables, namely the variable internship (X) and the variable career planning (Y). The population in this study were students of the 2019 Cosmetology and Beauty Department, Padang State University. The sample in the study was 37 students from the 2019 class of beauty and cosmetology department who were taken by random sampling. Data collection on educational variables used documentation data, namely internship value data and on career planning variables using questionnaires. Data analysis used product moment correlation analysis to determine the correlation between intership and career planning. The results of the data analysis show that the value of the correlation coefficient (r) between the variables of education and student career planning is 0.597 and the p value is 0.0000. The determinant value (r2) is 35.7%, so this indicates that internship makes a positive and significant contribution to student career planning. It can be concluded that: there is a positive and significant correlation between internship with career planning for students of the Cosmetology and Beauty department class of 2019, Padang State University. The results of this study can be used as material for consideration for lecturers of the Cosmetology and Beauty department in improving the educational quality of student skills and student career planning through the learning process, and for universities as material for consideration in curriculum development to improve the quality of student education.